What drives asset and resource stranding in the transition from fossils to clean energy? a systematic review - Rochelle Gladys Kemitare; Mary Nantongo; Charlotte Nakakaawa-Jjunju; Nicholas Mukisa; Francis Wasswa; Muyiwa S. Adaramola; Muyiwa S. Adaramola (Frontiers in Energy Research, 2025)
The study investigates the drivers and mechanisms of asset and resource stranding in the context of energy transitions. A systematic review approach was used to analyze existing studies, identify the drivers of energy resource and asset stranding, and examine their underlying mechanisms. The results show a regional bias, with most studies on stranded energy resources and assets conducted in Europe. Key factors influencing asset stranding are linked to policies, institutional frameworks, economic mechanisms such as shifts in investments toward clean technologies and divestment from fossil fuels and technological advancements related to increased accessibility of renewable energy technologies. Environmental risks also dynamically facilitate the stranding of fossil fuel assets. These findings suggest a critical research gap in understanding the drivers and mechanisms of asset and resource stranding in developing economies, particularly in Africa and Asia. Limited studies have explored asset-stranding dynamics in these regions, undermining the understanding of their unique challenges and opportunities for managing energy transitions effectively. Additionally, the interdependencies between these drivers and their cumulative effects remain underexplored, highlighting the need for more integrated and cross-disciplinary analyses. The findings of this study contribute to our understanding of asset and resource stranding and have implications for informing effective energy transition strategies in these less-studied regions.